2018
DOI: 10.18388/abp.2018_2649
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Triglycerides to High-Density Lipoprotein Cholesterol ratio (TG/HDL-C) in prediction of metabolic syndrome in Polish obese children and adolescents

Abstract: The triglycerides to high-density lipoprotein cholesterol ratio (TG/HDL-C) is a useful surrogate marker of insulin resistance and cardiovascular risk factors. We aimed to assess the relationship between the TG/HDL-C ratio and insulin resistance (IR) and its usefulness in prediction of the metabolic syndrome (MS). This retrospective study involved 122 obese children with the mean age of 11.6±3 years and their 58 healthy lean peers. Anthropometric measurements, blood pressure, the plasma lipid profile and oral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 26 publications
3
26
0
3
Order By: Relevance
“…The utility of TG : HDL-C ratio in predicting IR among children with obesity has been reported in prior studies [11, 14, 28, 29]. Similarly, studies have also shown the use of TG : HDL-C ratio in identifying children at risk for MetS [14, 30, 31]. In this study, we found that TG : HDL-C ratio ≥1.11 (sensitivity = 42.7%, specificity = 74.8%) separated children with the highest tertile of TG : HDL-C ratio from the remaining two-thirds.…”
Section: Discussionmentioning
confidence: 88%
“…The utility of TG : HDL-C ratio in predicting IR among children with obesity has been reported in prior studies [11, 14, 28, 29]. Similarly, studies have also shown the use of TG : HDL-C ratio in identifying children at risk for MetS [14, 30, 31]. In this study, we found that TG : HDL-C ratio ≥1.11 (sensitivity = 42.7%, specificity = 74.8%) separated children with the highest tertile of TG : HDL-C ratio from the remaining two-thirds.…”
Section: Discussionmentioning
confidence: 88%
“…Other abnormalities typical of metabolic syndrome, i.e., low HDL cholesterol and high triglycerides, are surrogate markers of IR and relatively low muscle mass [41]. Overall, the prevalence of metabolic syndrome among adolescents with PH was within the range of 15-20%, in comparison with 0.2-2.8% depending on age, in the general paediatric populations of European countries (IDF definition) [42][43][44][45]. In the USA, using the definition formulated by Cook et al, metabolic syndrome was diagnosed in up to 8.6% of young people from the general population, more commonly among males [46].…”
Section: Metabolic Abnormalities and Metabolic Syndrome In Adolescentmentioning
confidence: 99%
“…The above-described main abnormalities found in children with PH and typical of metabolic syndrome, immune activation, and sympathetic drive, are closely associated with TOD. It has been documented that the prevalence of left ventricular hypertrophy (LVH) correlates with the exposure to metabolic syndrome criteria, and severe LVH was found only in hypertensive patients who suffered from metabolic syndrome [42]. Similarly, subclinical hypertensive arterial injury, expressed as increased carotid intima-media thickness (cIMT), correlates with lower adiponectin concentrations and higher inflammatory activity [42,65].…”
Section: Metabolic Syndrome Associated Immune and Developmental Altementioning
confidence: 99%
“…Additionally, they found that HDL-C levels (<0.35 g/l), VLDL-TG levels (>0.656 g/l) can predict the presence of atherosclerotic plaque. In recent years, emerging studies have shown that the TG:HDL ratio can replace HOMA-IR and become a sensitive biomarker for early prediction of insulin resistance and cardiometabolic risk in obese people ( 37 39 ). Studies have highlighted that HDL can inhibit lipid oxidation and rebuild endothelial cells’ function, and has shown anti-inflammatory and anti-apoptotic activities in animal models ( 40 ).…”
Section: Discussionmentioning
confidence: 99%